0733 Retrospective Pain Reports In OSA Patients: Roles Of Depressive Symptoms, Polysomnographic And Self-report Sleep Measures. (27th May 2020) - Weingarten, J A; Dubrovsky, B; Cunningham, J; Chin, W; Howladar, A; Gikashvili, L
Abstract: Introduction: Exploring the relationship between OSA and pain, some studies showed hyperalgesia, and others, hypoalgesia. It was proposed that apnea-related sleep fragmentation causes hyperalgesia, and hypoxemia, hypoalgesia. However, SpO2 nadir had opposite relationships with pain measures in different studies. A 2018 review of over 1000 studies reported lack of consistent relationship between OSA and pain variables. Further, OSA was shown to relate to depressed mood, which may alter pain perception. Presently, retrospective reports of pain are analyzed as a function of polysomnographic and self-report sleep variables and depressive symptomatology in patients evaluated for OSA. Methods: A total of 1, 166 patients (923 women, 1136 minorities, 18-97 y.o., age M=53.1±15.2, BMI M=34.4±8.7) undergoing an overnight PSG filled out the Center for Epidemiologic Studies Depression Scale-Revised (CESDR), ISI, PSQI, ESS, and Chronic Pain Grade Scale yielding pain intensity (PI) and functional effect (FE) scores. PI and FE were separately regressed onto age, sex and BMI, followed by PSG and self-report variables meeting p<0.1 criterion. AHI and SpO2 nadir were forced into the models. Results: Mean AHI=29.6±34.7, range 0-167/hr, 72.3% had AHI≥5. Higher PI related to higher AHI (p=0.005, R 2 <1%), lower total arousal index (TAI, p=0.006, R 2 <1%), higher total sleep time (TST, p=0.003, R 2 <1%), higher PSQI (p<0.001, R 2 =5%), and higher CESD (p=0.001, R 2 <1%), without interactions with sex. Higher FE related to higher AHI (p=0.004, R 2 <1%), lower TAI (p<0.001, R 2 =1%), higher PSQI (p<0.001, R 2 =3%, and higher CESD (p<0.001, R 2 =2%). Sex had a significant interaction only with AHI (p=0.032); the FE-AHI relationship was significant in women (p=0.012), but not in men. Conclusion: On retrospective reports of pain in this large sample, higher AHI related to greater pain intensity in both sexes and to greater functional effect in women only. Unexpectedly, higher pain measures were also related to lower TAI and higher TST. Higher depressive symptomatology and subjective sleep disturbance on PSQI were related to greater pain intensity and its functional effect. Only a small portion of the variance in pain measures was accounted for by PSG and self-report variables. Support: none